Development of Educational Game Learning Media with An Ethnomathematics Approach Based on Banyumas Culture to Improve Students’ Mathematical Understanding Skills - Kumala, Fitria Zana; Agarica, Filamenta; Gunawan, Gunawan (AlphaMath : Journal of Mathematics Education, 2024)
The background of this research is the low mathematical understanding skills of seventh-grade students at SMP Negeri 1 Ajibarang. This study aims to develop educational game learning media with an ethnomathematics approach based on Banyumas culture in Geometry material that is valid and effective in improving mathematical understanding skills. The research method used Research and Development (R&D) with the ADDIE model. The population of this study includes all seventh-grade students, and the sample used in this study consists of class VII-B as the experimental class and class VII-A as the control class, with each class comprising 34 students. The results of this study indicate that the educational game learning media with an ethnomathematics approach based on Banyumas culture in Geometry material is valid, with an average percentage of 90.48% from material experts, 92.50% from media experts, 83.08% from mathematics teachers, 93.67% from small group trials, and 88.13% from field trial. The educational game learning media with an ethnomathematics approach based on Banyumas culture is also declared effective in improving students' mathematical understanding skills in Geometry material, as evidenced by the t-test result Sig. (2-tailed) = 0.000 < 0.05. Since the average N-Gain score of the experimental class is 0.73, which is higher than the average N-Gain score of the control class, which is only 0.43, it can be concluded that the educational game learning media with an ethnomathematics approach based on Banyumas culture is effective in improving the mathematical understanding skills of seventh-grade students in Geometry.